A Two-Year Stretch: The Functions of an Identity Workspace in Mid-Career Identity Work by Management Academics. (October 2014) - Haynes, Kathryn; Grugulis, Irena; Spring, Martin; Blackmon, Kate; Battisti, Giuliana; Ng, Irene
This article examines the way in which identity workspaces function to facilitate and stimulate transitions at mid-career. We explore our collective experience as a cohort of a mid-career management academics participating in a 2-year fellowship program, which acted as an identity workspace in which mid-career identity work took place. Using insights from our narratives, interviews, and experiences, we demonstrate how the fellowship provided rites of passage, experimentation, and social defenses, and we analyze our identity work, in relation to mid-career development, disciplinary orientation, and relationships with existing institutions. We conceptualize the identity workspace as a liminal zone in which to experiment with provisional selves, finding that identity workspaces function through alterity as well as identity, and at a communal as well as individual level. The article draws out the challenges for the academic community to facilitate mid-career identity work experienced in this identity workspace within existing institutions.